Comparison of hepatic proliferative activity in chronic hepatitis B and C - S. SARIOĞLU; Ö. GÖNEN; A. KÜPELİOĞLU; İ. ŞİMŞEK; E. TANKURT; S. AKTAŞ; H. ABACIOĞLU; H. AKBAYLAR; A. KILIÇALP; Ö. SAĞOL; G. ATAÇ; N. ÇULHACI; et al. (Turkish Journal of Gastroenterology, 2019)
-